THE MODERATING ROLE OF EMOTIONAL VALUE BETWEEN SOCIAL MOTIVATION AND SATISFACTION: AN EMPIRICAL STUDY OF CHINESE DATING SHOW AUDIENCES - Zhang , Shasha; Yasin, Megat Al Imran; Ng , Chwee Fang (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2025)
With the rapid rise and immense popularity of dating reality shows in the Chinese media landscape, understanding the underlying psychological drivers of audience engagement has become crucial for deciphering their success. Grounded in the Uses and Gratifications Theory (UGT), this study constructs and empirically tests a model examining the relationships between social motivation, emotional value, and audience satisfaction. It specifically investigates the moderating role of emotional value within this dynamic. A structured questionnaire survey was administered to 591 Chinese viewers of popular dating shows. Data analysis using hierarchical regression revealed several key findings: (1) Social motivation, manifested through behaviors such as social discussion and interaction, exerts a significant positive influence on audience satisfaction. (2) Emotional value, derived from content through emotional resonance and affective involvement, directly and significantly enhances satisfaction. (3) Most importantly, emotional value serves as a positive moderator in the relationship between social motivation and satisfaction. This indicates that the positive effect of social motivation on satisfaction is significantly stronger for audiences who experience higher levels of emotional value from the program. The study elucidates the critical "amplifier" role of emotional experience, suggesting that content which successfully elicits strong emotions can substantially magnify the satisfaction gained from social utility. These findings offer valuable theoretical extensions to UGT in the context of new media entertainment and provide practical insights for content creators and platform operators seeking to optimize engagement strategies by strategically integrating social hooks with potent emotional design.